A educação a distância como apoio à implantação de um trânsito cidadão: a experiência da cidade de São Paulo - Kiefer, Josefina Giacomini (2015)
This study describes and analyses the programs of the courses taught at a distance for training the teachers, mediated by computers and internet, developed by the Companhia de Engenharia de Tráfego de São Paulo - CET, as a subsidy for the construction of knowledge and the realization of educative actions focused on the traffic theme and with a purpose of non-formal education in the tuition of basic education teachers in the city of São Paulo. Since the mid of the 1970's, CET develops attendance programs on the non-formal education, with the goal of spread the knowledge and teach the practices that involves the sharing of the public space of the São Paulo city in a citizen and safe way for everybody. Since 2009, attentive to the social and educational context that shows an increasingly use of the Information and Communication Technologies (TIC), the company starts studying the utilization of these tools in its educational programs, resulting, in 2010, in the implementation of the first course at a distance, whose target audience was the teachers of the second cycle of fundamental education and the education for adults. Since these first experience, which was successful, seven other courses were developed until the mid of 2012, being five of these courses focused on the tuition of teachers. The specific goals for this research contemplates the investigation about the perception of the teachers about the contribution of the content of the courses taught by CET in the modality of teaching at a distance for their professional development and for the development of their own projects related to the traffic in their disciplines, identifying the needs and expectations provided by them; the analysis and identification of dialogues, in the interface between the students and the tutors of the courses at a distance of CET, which shown an involvement and a participation of the student in the theme traffic , citizenship, environment and art/education and in which form they express the possibility or the use of these themes in their practices; the identification about the approach of the themes citizenship, environment and art/education in the projects developed by the teachers that participate of the courses at a distance of CET; the thinking about the use of education at a distance in subjects related to the education of teachers. The methodological procedures involve the application of a questionnaire for the teachers, interviewing via telephone and analyzing the discussion forums. The period was since July of 2010 until December of 2012. The research pointed out that the results were satisfying in what relates to the perception of the teachers about the structure of the courses and the importance of the offered content, indicating the use of the discussed themes in the conception of projects in the school units. The analyze of the dialogues between students and tutors provides results that indicates the need of improvements, in the sense of a better utilization of the discussion forums space and for the construction of a knowledge related to education for the traffic, citizenship, environment and art/education.